GREEN MANAGEMENT SYSTEM - Hasan, Ali (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Green Management System (GMS) is an effort to protect the environment. With the depletion of natural resources, the protection of the environment is not only limited to a small part of its corporate social responsibility, but it must be a model in business organizations. Model GMS-oriented environment, will systematically affect the company in reducing waste, reducing the use of natural resources, reduce pollution and continuously monitoring the purpose of creating business results were positive for all stakeholders. Modern business travel will continue to come under pressure from the environment and the realization of the company's sustainability strategy, the managers began to review the possibility of implementation of GMS in the management system of the organization; directs the management of the organization, developing technologies to reduce adverse environmental impact and develop the production of green (green production) more rational and cost-effective. Development and implementation of green policies in environmental management becomes an important part of the transformation of business management functions in optimizing the use of GMS to improve corporate performance and benefits for environmental sustainability. Direct implications for the development and implementation of environmental protection in the modern business organization in accordance with modern green standards and the principles of environmental sustainability and a company associated with the creation of the organization, program and structure, education and training of human resources will enable the transfer and dissemination of knowledge for environmental protection. Keywords: Green Management Systems, Green Production, Sustainability company and Environment